2018
DOI: 10.1503/cjs.010114
|View full text |Cite
|
Sign up to set email alerts
|

Is radiofrequency ablation of varicose veins a valuable option? A systematic review of the literature with a cost analysis

Abstract: Background: Since the 1990s, new techniques for the treatment of varicose veins have emerged, including radiofrequency ablation (RFA) and laser treatment. We performed a study to compare the safety, efficacy and outcomes of RFA compared to those of open surgery and laser ablation for the treatment of varicose veins. We also carried out a cost analysis of RFA compared to open surgery to assess whether RFA could help free up operating room time by being performed in an outpatient context. Methods:We conducted a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 66 publications
0
12
0
2
Order By: Relevance
“…Studies on this topic unanimously report that, regardless of treatment method, the outcome is very favorable and venous symptoms are almost completely resolved with treatment [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on this topic unanimously report that, regardless of treatment method, the outcome is very favorable and venous symptoms are almost completely resolved with treatment [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…As of 1990 there are scientific works that demonstrate that the RFA is a safe and effective method to abolish the reflux of the saphenous vein [15], as described by Merchant RF, et al in which complete improvement of saphenous vein insufficiency is reported greater with RFA (between 90 and 100%) of the cases, making follow-ups between three months and four years [14,16]. RFA equals conventional surgery in efficacy but it is also clearly superior in terms of less postoperative pain, better quality of life and faster recovery [17,18].…”
Section: Efficacy Of Radio Frequencymentioning
confidence: 99%
“…Studien und Publikationen zu dem Risiko postoperativer tiefer Beinvenenthrombosen nach endovenösen thermischen Ablationen, beschreiben ein Thromboserisiko von ca. 1-1,8 % [11][12][13]. Das ist ein deutlich höheres Thromboserisiko als nach der klassischen operativen Sanierung der Varikosis.…”
Section: Postoperative Thromboseunclassified
“…In der Publikation von Poder et al wird das Infektionsrisiko der endovenösen Radifrequenzablation mit 0,4 % angegeben [13]. Weitere Literaturangaben zum Infektionsrisiko bei endovenösen Verfahren und Sklerosierungsbehandlung sind schwer zu finden.…”
Section: Infektionsrisikounclassified